Sauer's manual of skin diseases - Hall, Brian J. (Brian John) 1981-; Hall, John C. 1947-.; Sauer, Gordon C. (Gordon Chenoweth) 1921- (Philadelphia Wolters Kluwer Health/Lippincott Williams & Wilkins, 2010)
This book provides step-by-step instructions and algorithms for diagnosis and treatment of all common skin conditions. Unique features include more than 700 full-color photographs; diagnostic algorithms based on site and type of lesion and age of patient; and a comprehensive dictionary-index of skin diseases. This thoroughly revised, updated Tenth Edition includes new chapters on sexually transmitted infections, non-melanoma skin cancer, vascular tumors, cutaneous T-cell lymphoma, skin diseases in ethnic skin, obesity and dermatology, skin diseases in transplant patients, and nutritional and metabolic diseases and the skin.
Structure of the skin -- Laboratory procedures and tests -- Dermatologic diagnosis -- Dermatologic therapy -- Technologic applications in dermatology -- Fundamentals of cutaneous surgery -- Cosmetics for the physician -- Dermatologic allergy -- Immune-mediated skin diseases -- Atopic dermatitis -- Pruritic dermatoses -- Vascular dermatoses -- Seborrheic dermatitis, acne, and rosacea -- Psoriasis -- Other papulosquamous dermatoses -- Granulomatous dermatoses -- Dermatologic parasitology -- Bullous dermatoses -- Exfoliative dermatitis -- Psychodermatology -- Dermatologic bacteriology -- Spirochetal infections -- Dermatologic virology -- Cutaneous diseases associated with human immunodeficiency virus -- Dermatologic mycology -- Sexually transmitted infections -- Tumors of the skin -- Non-melanoma skin cancer -- Melanoma -- Vascular tumors -- Cutaneous T-cell lymphoma -- Diseases affecting the hair -- Diseases affecting the nail unit -- Diseases of the mucous membranes -- Skin diseases in ethnic skin -- Pigmentary dermatoses -- Collagen-vascular diseases -- The skin and internal disease -- Dermatologic reactions to ultraviolet radiation and visible light -- Genodermatoses -- Pediatric dermatology -- General principles of skin aging -- Obesity and dermatology -- Skin disease in transplant patients -- Tropical diseases of the skin -- Sports medicine dermatology -- Cutaneous signs of bioterrorism -- Dermatoses of pregnancy -- Nutritional and metabolic diseases and the skin -- Where to look for more information about a skin disease.
Includes bibliographical references and index.
Keywords: Skin -- Diseases -- Handbooks, manuals, etc; Skin Diseases; Handbooks and manuals